A personal local area information interaction system based on NFC and Bluetooth technology. (16th April 2019) - Wang, Tian; Zhou, Jiyuan; Wang, Wenhua; Zhang, Guangxue; Huang, Ming; Lai, Yongxuan
Taking attendance is a regular activity in the society. Required class attendance is common in Chinese colleges and universities. In most of the traditional classroom, taking attendance may consume much time and some students may cheat by pretending to be their classmates, which makes the results unbelievable. Moreover, the interaction mode between the teacher and students is single and cannot support fast data interaction. To solve these problems, this paper proposes an information interaction system, which cannot only speed up the process of taking attendance but also extend the information exchange mode. Firstly, we propose the near field communication (NFC)-based method to take attendance, which utilises the rapid information exchange characteristic of NFC in the mobile phone. Furthermore, an ad hoc scheme is introduced, based on which some students may be selected as the relay which can greatly accelerate the attendance taking process. Moreover, a lazy unbinding mechanism is proposed to prevent the students from taking attendance for others. Finally, based on Bluetooth technology the system realises file transfer, which extends the information exchange mode. Real experimental results demonstrate the feasibility of the proposed system.